Celovit sistem za upravljanje voznega parka v potniškem prometu - Igrec, Dalibor (Zbornik mednarodne Elektrotehniške in računalniške konference, 2018)
In order to increase or at least sustain the quality of live for citizens and visitors, improving management capabilities of the services is a necessary task of everyone involved in urban planning. With the rising city population and urbanization smart managing of city services becomes more and more important. Public transit, as one of the most important city services, stands to gain the most from the introduction of the smart management system. This article presents solution called comprehensive fleet management system for passenger transport. Featured example is based on management of bus transit services. Presented solution is comprised of mobile units, installed in bus vehicles and platform acting as central back-office processing system. Key tasks of the platform are managing communication with mobile units and performing data processing. Platform also contains web applications and interfaces for operational management, communicating with drivers and supporting services as well as interfaces for third party integration, such as time schedules, mobile planners etc.
Keywords: javne storitve; javni prevozi; menedžment podatkov; upravljanje s sistemi